Three dimensional analysis of dental arch form and dimensions in a sample of Kurdish students in Hawler Medical University. - Barzan Mahmood; Bayan Hassan (Erbil Dental Journal)
Background: This study aims to use 3D analysis to compare male and female upper and lower dental arch forms in untreated Kurdish medical students, find differences in shape, transversal and longitudinal diameters between genders, and provide clinicians with a representative set of the population's dental arch to provide appropriate orthodontic treatment.